2005
DOI: 10.1016/j.febslet.2005.09.086
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dinuclear metal center of Pyrococcus furiosus prolidase by analysis of targeted mutants

Abstract: Prolidases are dipeptidases specific for cleavage of Xaa-Pro dipeptides. Pyrococcus furiosus prolidase is a homodimer having one Co-bound dinuclear metal cluster per monomer with one tightly bound Co(II) site and the other loosely bound (K d 0.24 mM). To identify which Co site is tight-binding and which is loose-binding, site-directed mutagenesis was used to modify amino acid residues that participate in binding the Co1 (E-313 and H-284), the Co2 site (D-209) or the bidentate ligand (E-327). Metal-content, enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In hRecProl-G448R the kinetic parameters were indicative of a substantial active site structural perturbation, while the results on the hRecProl-231delY suggested that the deletion may perturb the substrate positioning/access to the catalytic site with a consequent decrease in the rate of catalysis. For the hRecProl-E412K, a higher K M value indicated that, besides being a ligand of the metal [38], residue 412 may also be involved in substrate binding/access.…”
Section: Discussionmentioning
confidence: 99%
“…In hRecProl-G448R the kinetic parameters were indicative of a substantial active site structural perturbation, while the results on the hRecProl-231delY suggested that the deletion may perturb the substrate positioning/access to the catalytic site with a consequent decrease in the rate of catalysis. For the hRecProl-E412K, a higher K M value indicated that, besides being a ligand of the metal [38], residue 412 may also be involved in substrate binding/access.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that cobalt ion can often substitute for zinc in vitro, giving comparable or higher levels of enzyme activity, is known (14,15) and suggests that cobalt and zinc can bind to similar motifs. In fact, Glu, Asp, and His were shown to coordinate Co 2ϩ in the cobalt-dependent prolidase of Pyrococcus furiosus (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria and archaea, prolidase is thought to function in the degradation of intracellular proteins and in proline recycling in concert with other endo‐ and exopeptidases (Du et al. 2005).…”
Section: Introductionmentioning
confidence: 99%